An investigation into the overheating risk in low-energy new-built homes - Sougkakis, Vasileios (2017)
Recently, overheating in British housing has received increased attention due to climate change and consequent impact on the thermal comfort and the health of building occupants. The risk of overheating becomes even larger considering the requirements for higher insulation and airtightness levels set by building regulations. Passive design strategies, such as the use of thermal mass and ventilation, for regulating indoor temperatures may improve the thermal comfort of occupants without the use of energy intensive equipment. Modern Methods of Construction (MMC) are expected to play a significant role in the future outputs of the housing construction sector. However, MMC, which generally present low levels of thermal mass, are treated with scepticism by designers since they are considered to be more prone to overheating compared to masonry constructions. Due to the lack of extensive research data on the thermal performance of these systems, however, it can be inferred that concerns may be based on the perception of the industry rather than actual data. Therefore, the work presented in this thesis investigated the risk of overheating in dwellings built with MMC. The analysis considered the performance of the constructions from various perspectives following a route from the general investigation to the more specific characteristics of the building elements. First, an investigation of the zone temperatures obtained through monitoring and through whole building dynamic simulations was performed, in an attempt to evaluate the relative performance of different construction types and building elements. Next, the interaction of the various building elements with their surrounding space was assessed through monitoring the heat flows and the temperatures on the surface of these elements in situ. Finally, a more detailed investigation of the dynamic characteristics of these elements under fixed conditions was conducted through laboratory testing and Finite Element Analysis (FEA). A parametric simulation study of ambient temperatures in a timber frame building considered the potential to use non-traditional materials for regulating internal temperatures. Results showed that overheating was an issue in most of the zones examined for the conventional timber frame construction. The use of additional materials resulted in reduced overheating levels of up to 85% in some cases; this evidence may be used to inform designers when considering measures to reduce the overheating risk of MMC. In another study of two houses built with different construction methods, it was found that the timber frame and modern masonry walls had very similar performance, with the latter presenting slightly reduced levels of overheating in some cases (up to 12% lower compared to timber frame). Monitoring the heat flows at the surface of the building elements in situ as well as through laboratory testing and FEA showed that difference in performance between masonry constructions and MMC was not always as clear as expected from the construction characteristics of the elements. It was clear that conventional masonry constructions do not benefit fully from the increased mass and had comparable performance with some MMC. Phase Change Materials (PCM) were also found more responsive than conventional plasterboard in situ, although some discrepancy compared to the theoretical performance was identified. The findings of this study may be useful for designers so that optimum use of the benefits of thermal mass is made.